The effects of histone crotonylation and bromodomain protein 4 on prostate cancer cell lines - Xu, Xiaolin (Transl Androl Urol, 2021)
BACKGROUND: The aims of this study were to detect the level of histone crotonylation in prostate cancer (PCa) tissues, analyze the correlations between its level and clinical stage and grade, and explore the effects of bromodomain-containing protein 4 (BRD4) inhibitors and sodium crotonate on the histone crotonylation in PCa cell lines and on the functions of PCa cells. METHODS: PCa tissues from 72 patients and adjacent tissues from 7 patients were collected, and immunohistochemistry was used to measure the level of histone crotonylation. Three human PCa cell lines, PC-3, LNCaP, and C42B, were selected and treated with IC50 value of I-BET762, I-BET726, and CPI-203, respectively. Next, short hairpin RNA (shRNA) transient knockdown was used to inhibit BRD4 expression. Histone crotonylation level and the expression of acetylase were determined by Western blotting. Finally, cell proliferation, migration, and invasion were measured with Cell Counting Kit-8 assay, scratch test, and Transwell test respectively. RESULTS: The level of histone crotonylation in PCa tissue was higher than that in adjacent tissues, and histone lysine crotonylation (Kcr) increased with the increasing malignancy of PCa. Treatments with I-BET762, I-BET726, and CPI-203 could inhibit the proliferation, migration, and invasion of PCa cell lines including PC-3, LNCaP, and C42B, and could also regulate the histone crotonylation and androgen receptor signaling pathways via the regulation of BRD4 expression. CONCLUSIONS: PCa is closely related to histone crotonylation. Inhibition of BRD4 expression can inhibit the proliferation, migration, and invasion of PCa cells.